2018
DOI: 10.3389/fmars.2018.00208
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Relative Abundance and Size of Snapper Chrysophrys auratus Within Partially-Protected and No-Take Areas in a Temperate Marine Protected Area

Abstract: Marine Protected Areas (MPAs) are known to contribute toward the conservation of marine biodiversity, particularly targeted fishery species. Snapper Chrysophrys auratus are an important recreational and commercial fish species in New South Wales (NSW), Australia, and despite fishery management for this species, they are considered "growth overfished" in this region. To assess how C. auratus respond to the implementation of an MPA with several no-take and partially protected areas in temperate NSW, we monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Data were examined on fishing activity in two NTAs in the Port Stephens–Great Lakes Marine Park (PSGLMP) in New South Wales (NSW), Australia, to improve understanding about the influence of how short‐term temporal factors influence illegal fishing in NTAs. The PSGLMP is a popular region for recreational fishing (Read, West, Haste, & Jordan, ) and is an important area for fishery target species such as snapper Chrysophrys auratus (Forster), which are in high relative abundance in NTAs compared with fished areas (Harasti, Davis, Mitchell, Lindfield, & Smith, ; Harasti, Williams, Mitchell, Lindfield, & Jordan, ) and also display strong site fidelity within a NTA (Harasti, Lee, Gallen, Hughes, & Stewart, ). A study by Harasti et al () reported illegal recreational fishing within a NTA reduced both the size and abundance of C. auratus .…”
Section: Introductionmentioning
confidence: 99%
“…Data were examined on fishing activity in two NTAs in the Port Stephens–Great Lakes Marine Park (PSGLMP) in New South Wales (NSW), Australia, to improve understanding about the influence of how short‐term temporal factors influence illegal fishing in NTAs. The PSGLMP is a popular region for recreational fishing (Read, West, Haste, & Jordan, ) and is an important area for fishery target species such as snapper Chrysophrys auratus (Forster), which are in high relative abundance in NTAs compared with fished areas (Harasti, Davis, Mitchell, Lindfield, & Smith, ; Harasti, Williams, Mitchell, Lindfield, & Jordan, ) and also display strong site fidelity within a NTA (Harasti, Lee, Gallen, Hughes, & Stewart, ). A study by Harasti et al () reported illegal recreational fishing within a NTA reduced both the size and abundance of C. auratus .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we have added to the relatively well established body of literature documenting the positive effects that the establishment of no‐take marine reserves has on the abundance of fish targeted by anglers (e.g. Evans & Russ, ; Harasti et al, ; Lester et al, ; Williamson et al, ; Willis et al, ). We also found, not surprisingly, that different species of fish appear to respond differently to changes in temperature and that the responses of suites of species of fish to changing temperature may be relatively complex and unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…Marine Protected Areas (MPAs), which include 'no-take' zones, of appropriate habitat configuration and size have been shown to be highly effective tools for conserving fish biodiversity, and for the sustainable management of fish populations, including relatively small New Zealand marine reserves (Babcock, Kelly, Shears, Walker, & Willis, 1999;Shears & Babcock, 2002). Not only are the individuals of species targeted by fishers generally more abundant and larger in no-take zones (Evans & Russ, 2004;Harasti, Williams, Mitchell, Lindfield, & Jordan, 2018;Williamson, Russ, & Ayling, 2004;Willis, Parsons, & Babcock, 2001), but increasingly no-take zones are being shown to provide recruits to adjacent over-fished areas (Pillans et al, 2005;Russ, Alcala, & Maypa, 2003).…”
mentioning
confidence: 99%
“…Temperate HPMAs have been found to show similar, positive biological responses for reef habitat compared with tropical ones (Stewart et al, 2009;Harasti et al, 2018). Positive biological responses have also been shown to be greater in HPMAs than in areas receiving less protection.…”
Section: Ecological Effectsmentioning
confidence: 93%
“…On average, many fish, invertebrate and seaweed species increase in biomass, density, size and species diversity inside tropical and temperate HPMAs (Lester et al, 2009;Fenberg et al, 2012, Sciberras et al, 2013Edgar et al, 2014, Guidetti et al, 2014Di Franco et al, 2016, Harasti et al, 2018. Some fish and invertebrate species decline inside HPMAs as a result of competitive or predatory interactions (Micheli et al, 2004).…”
Section: Species and Habitat Ecosystem Servicesmentioning
confidence: 99%